Estimation of the Heat Flow Variation in the Chad Basin Nigeria - NC Nwankwo; AS Anthony; LI Nwosu (Journal of Applied Sciences and Environmental Management, 2010)
Wireline logs from 14 oil wells from the Nigerian sector of the Chad Basin were analyzed and interpreted to estimate the heat flow trend in the basin. Geothermal gradients were computed from corrected bottom hole temperatures while the bulk effective thermal conductivity for the different stratigraphic units encountered in the wells were computed from the sonic logs data. The heat flow values were then calculated. A corrected average geothermal gradient of 3.4 oC/100 m and a regional range of 3.0 to 4.4 oC/100 m were obtained. A porosity range of 2 to 79 % and average of 35 % were computed for Chad Basin Nigeria. Also the thermal conductivities vary from 1.70 and 3.11 Wm-1 oC-1, with an average value of 2.35 Wm-1 oC-1 computed for the various wells in the basin. A large variation in heat flow was recorded within the basin. Mean heat flow values computed for the basin vary from 63.6 to 105.6 mWm-2, with a simple average of 80.6 mWm-2. Although there is no distinct trend on heat flow within the basin, the computed heat flow values are relatively lower at the southwestern and northeastern axis of the basin. And the values obtained in this study compared favorably with those of other world sedimentary basins (including Niger Delta) that are of similar history with the Chad Basin, suggesting that the Nigerian Chad Basin is a possible petroliferous basin.